Odpowiedzi

2009-12-07T19:19:21+01:00
14 - 3y
x= --------
2

3 * (14-3y/2) - 2y = 8
42-9y/2 - 2y = 8 /*2
42 - 9y - 4y = 16
42 - 16 = 13y
26 = 13y
y = 2

x= 14 - 3*2 / 2
x= 14 - 6 / 2
x= 8/2 = 4

y=2
x=4
2009-12-07T19:19:34+01:00
2x + 3y =14
3x - 2y = 8

2x=14-3y /2
3x-2y=8

x=7-1,5y
3(7-1,5y)-2y=8

x=7-1,5y
21-4,5y-2y=8

x=7-1,5y
-6,5y=-13 /(-6,5)

x=7-1,5y
y=2

x=7- 1,5(2)
y=2

x=4
y=2
2009-12-07T19:24:03+01:00
2x+3y=14/-3y
3x-2y=8

2x=14-3y /:2
3x-2y=8

x=7-1,5y
3(7-1,5y)-2y=8

x=7-1,5y
21-4,5y-2y=8

x=7-1,5y
21-6,5y=8/-21

x=7-1.5y
-6,5y=-13/:6,5

x=7-1,5y
y=2

x=7-1,5*2
y=2

x=7-3
y=2

x=4
y=2